2008
DOI: 10.1007/s00726-008-0114-x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative application of l-alanyl-l-glutamine in cardiac surgery: effect on the polarized T cell cytokine expression

Abstract: At risk patients undergoing cardiac surgery with cardiopulmonary bypass have increased rates of postoperative infectious morbidity. Postoperatively, after cardiac surgery, an immunosuppression in the form of a polarization of T helper (Th) cells with a decreased Th1 response (IL-2 and IFN-gamma) and an increased Th2 response (IL-4 and IL-10) is recognized. Therapeutic strategies to modulate the immunological response include special key nutrients such as the amino acid glutamine favoring the Th2 response. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…l -alanyl- l -glutamine has been widely used in clinic as a way to provide l -glutamine ( 33 ). Infusion with l -alanyl- l -glutamine (0.5 g/kg) per day has been reported ( 34 ). The highest dose of glutamine we used in vivo in this study was 100 mg/kg, much lower than the reported dose.…”
Section: Discussionmentioning
confidence: 99%
“…l -alanyl- l -glutamine has been widely used in clinic as a way to provide l -glutamine ( 33 ). Infusion with l -alanyl- l -glutamine (0.5 g/kg) per day has been reported ( 34 ). The highest dose of glutamine we used in vivo in this study was 100 mg/kg, much lower than the reported dose.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers used a high-dose L-alanyl-Lglutamine dipeptide (L-ALA-GLN) (0.5 g/kg/day GLN) after induction of anesthesia and continued it for three days. This action had only a minor influence on intracellular IL-2 and the expression of polarized intracellular T cell cytokine [93], and no effect on intracellular IL-1, IL-6, IL-8, and TNFα [92]. No other effects on C-reactive protein (CRP) level [92], mortality rate [93], postoperative infections number [93], vasopressor/inotropic support [92], ventilation time [92,93], renal function [93], SOFA score [92], and ICU length of stay [92] were found [93].…”
Section: Glutamine In Cardiac Surgery-the Clinical Experiencementioning
confidence: 98%
“…Engel et al ( 2009) studied the GLN supplementation in open cardiac surgery patients that fulfilled one of the following criteria: age over 70 years, ejection fraction less than 40%, or mitral valve replacement [91][92][93]. The researchers used a high-dose L-alanyl-Lglutamine dipeptide (L-ALA-GLN) (0.5 g/kg/day GLN) after induction of anesthesia and continued it for three days.…”
Section: Glutamine In Cardiac Surgery-the Clinical Experiencementioning
confidence: 99%
“…Markewitz et al found that IL-2 and IFN-γ secretion are diminished after cardiac surgery;15 conversely, Muret et al demonstrated that IL-4 and IL-10 production are elevated 16. Thus, the Th1 and Th2 responses are decreased and increased, respectively, after cardiac surgery 17. Fatty acids are classified into two main families of polyunsaturated fatty acids; ω-3 fatty acids, which include eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and the other is ω-6 fatty acids, which include linoleic acid (LA), arachidonic acid (AA), and γ-linolenic acid.…”
Section: Introductionmentioning
confidence: 99%
“…16 Thus, the Th1 and Th2 responses are decreased and increased, respectively, after cardiac surgery. 17 Fatty acids are classified into two main families of polyunsaturated fatty acids; ω-3 fatty acids, which include eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and the other is ω-6 fatty acids, which include linoleic acid (LA), arachidonic acid (AA), and γ-linolenic acid. Several studies have reported beneficial effects of preoperative supplementation with specialized diets enriched with ω-3 fatty acids, arginine, and RNA.…”
Section: Introductionmentioning
confidence: 99%